(untitled) (Shevchenko Studies, 2025)
The article deals with T. Shevchenko’s story "The Servant" as an experience of reading the history of Ukraine in a psychological way, in the context of the dynamics of mentality, local culture of the ethnos, people, folklore and ethnography. Through resentment as a suppressed revenge and resentment and melancholy as its experience in time, the emotional background, the anthropological codes of the enslaved Ukrainian nation are studied. Emotions serve as a tool for understanding and creative objectification of colonial trauma, speech codes of an inverted, inverted, oppressed and torn world. The narrator turns into a kind of antiquarian, collector, biographer and memoirist, who collects memories at the level of impressions and feelings, cinematically connects disparate fragments of space into a holistic picture of the Ukrainian world, correlating the fate of the veiled woman with the historical tragedy of Ukraine.